Prebiotic properties evaluation of red seaweed (Kappaphycus alvarezii) using in vitro colon model - Abang Bajury, Dayang Marshitah (2018)
The red seaweed Kappaphycus alvarezii is rich in carrageenan polysaccharides that are used in hydrocolloids industry for gelling and thickening agents in pharmaceutical, biotechnology and food application. It has been claimed that the carrageenan is not digestible by human. Present study builds on that knowledge to test the potential of red seaweed as a prebiotic through in vitro digestion and fermentation. The objectives of this study are to determine the digestibility of K. alvarezii through in vitro gastric and duodenal digestion, to analyze the metabolite short chain fatty acids (SCFAs) generated by the fermentation of seaweeds by using high performance liquid chromatography (HPLC) and to evaluate the fermentation selectivity of seaweeds by the human feces microbiota by using fluorescent in situ hybridization (FISH) technique. The digestibility of red seaweeds (Kappaphycus alvarezii) cultivated from Sabah (RSS) and Langkawi (RSL) was determined using in vitro gastric and duodenal digestion model that mimicking human gastrointestinal tract condition. The resulting fractions of seaweeds that resisted gastric and duodenal digestion were used as substrates for fermentation in pHcontrolled batch culture system inoculated with human feces to mimic human distal colon condition. Inulin was used as positive control and samples were taken at 0, 6, 12 and 24 h of fermentation for bacterial enumeration and SCFAs analysis. Red seaweed from Sabah (RSS) showed no significant difference with inulin for its non-digestibility while red seaweed from Langkawi (RSL) showed the highest digestibility (4.55%) by in vitro gastric and duodenal digestion. Both RSS and RSL showed significant increase of Bifidobacterium sp.; from log10 7.96 at 0 h to log10 8.72 at 24 h, and from log10 7.96 at 0 h to log10 8.60 at 24 h respectively, but at 24 h both seaweeds showed no significant difference when compared to the Bifidobacterium sp. count at the end of the inulin fermentation. The growth for Clostridium sp. in RSS (from log10 at 0 h 6.78 to log10 7.27 at 24 h) and RSL (from log10 6.78 at 0 h to log10 7.24 at 24 h) also showed no significant difference in comparison to inulin (from log10 6.78 at 0 h to log10 7.26 at 24 h). Inulin and RSS showed significant increase in total SCFA production after 24 h of fermentation, particularly in acetate and propionate. While for RSL, the total SCFA showed significant increased at 6 h, however, the total SCFA showed no significant difference after 12 and 24 h. Overall, this data suggested that RSS have potential as a prebiotic similar to the positive control, inulin compared to RSL. This is because RSS shows more bifidogenic factor and high total SCFAs production compare to RSL.